Maternal and Perinatal outcome in eclampsia at a teaching hospital of Eastern Nepal - Mishra, Seema Kumari; Pradhan, Roshan; Pradhan, Roshan; Pokharel, Hanoon P; Parajuli, Surya B. (Birat Journal of Health Sciences, 2020)
Introduction: Eclampsia is a multisystem disorder with potential life-threatening complications that can result in significant maternal and fetal morbidity and mortality. The case fatality rate of eclampsia is 1.8% in developed countries, 17.7% in India and 13% in Nepal. The incidence of pre-eclampsia and eclampsia is high in developing countries due to hypoproteinemia, malnutrition and poor obstetric facilities. Objective: To assess the maternal and perinatal outcome in patients of eclampsia Methodology: This was a hospital based cross-sectional study where all the patients presenting with eclampsia from June 2019 to November 2020 in the department of Obstetrics & Gynecology, Birat Medical College and Teaching Hospital were enrolled for the study. Data analyzed included various maternal parameters and fetal parameters along with the mode of delivery, outcome of baby, postpartum maternal condition and maternal mortality were noted. Results: Among 6631 deliveries, 50 patients had eclampsia with the incidence of 7.54/1000 deliveries. Thirty four (68%) patients were of 20-30 years of age, 37 (74%) were primigravidas, 36 (72%) from rural areas, 34 (68%) were illiterate, 49 (98%) were low to middle socioeconomic status, 41 (82%) were unbooked and 33 (66%) patients had antepartum eclampsia. Eleven (22%) women developed eclampsia related complications. There were 02 (4%) maternal deaths and the common causes were HELLP Syndrome and pulmonary oedema. Neonatal outcome consisted of live births in 39 (78%) newborns, 03 (6%) were still births, 08 (16%) were birth asphyxia and 15 (30%) were low birth weight. Conclusion: Majority of the patients were young, illiterate, unbooked primi gravidas with poor to average socioeconomic status from rural areas. Majority of the eclamptic women nearly 39 (78%) cases delivered via caesarean section for better neonatal outcome. Two (4%) eclamptic women died as a result of eclamptic complications and three (6%) newborns had neonatal deaths because of low birth weight and prematurity. Adequate antenatal screening, early detection of hypertension, timely referral, and early initiation of treatment and termination of eclamptic patients can help to improve the maternal and perinatal outcomes.